2002
DOI: 10.1183/09031936.02.01372002
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of diagnostic procedures for Pneumocystis carinii pneumonia in HIV-1-infected patients

Abstract: Sputum induction is a simple and noninvasive procedure for Pneumocystis carinii pneumonia (PCP) diagnosis in human immunodeficiency virus-1-positive patients, although less sensitive than bronchoalveolar lavage (BAL). In order to obtain an overview of the diagnostic accuracy of sputum induction, a systematic review and meta-analysis of studies reporting the comparative sensitivity and specificity of BAL (the "gold standard") and sputum induction was performed.The odds ratio and related 95% confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 68 publications
1
55
0
13
Order By: Relevance
“…Studies have shown that the organism is detectable on microscopic examination of induced sputum in 55-92% of PCP patients with HIV infection (39,40). In patients with PCP but without HIV infection, detectability is Ͻ10%; thus, bronchoalveolar lavage fluid examination is often required (38).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the organism is detectable on microscopic examination of induced sputum in 55-92% of PCP patients with HIV infection (39,40). In patients with PCP but without HIV infection, detectability is Ͻ10%; thus, bronchoalveolar lavage fluid examination is often required (38).…”
Section: Discussionmentioning
confidence: 99%
“…In AIDS patients, this technique has a 13% to 55.5% sensitivity and a 98.6% specificity; these figures could be improved if stained P. jiroveci detection was replaced with immunofluorescence (B). (71,72) In patients who are HIV-positive or have AIDS, non-induced sputum for the diagnosis of CAP is as effective as in HIV-negative patients (B). (73) In severe CAP patients with acute respiratory failure requiring intubation and mechanical ventilation, secretions collected via bronchial lavage without bronchoscopy and associated with semi-quantitative culture with a 10,000 colony forming units per milliliter threshold (10 4 CFU/mL) has good sensitivity, ranging from 58% to 83%, and is better than bronchoscopy lavage; additionally, it has the advantage of being noninvasive and easy to perform.…”
Section: Do the Respiratory Specimens Collecting Techniques Impact Thmentioning
confidence: 99%
“…In a meta analysis of diagnostic procedures for PcP, it was found that, compared with bronchoalvelaor lavage as the gold standard, examination of induced sputum had an overall sensitivity of 55.5% and a specificity of 98.6% with even better sensitivity at 67% versus 43.1% when comparing immunofluorescent staining with cytochemical staining. In settings where the prevalence of PcP is in the range of 25-60%, the positive and negative predictive values ranged from 86-96.7% and 66.2-89.8%, respectively, with immunofluorescent staining , and 79-94.4% and 53-83.5% with cytochemical staining 48 .…”
Section: Microbiological Testsmentioning
confidence: 99%